309 Neo-adjuvant chemotherapy for cervical cancer during pregnancy: a retrospective case series. (13th November 2020) - Lopez, A; Rodríguez, J; Estrada, E; Chavez, C; Amaro, C; Aragona, A; De Padua, C; Borges Garnica, A; Rendón, G; Almeciga, A; Serrano, O; Scasso, S; et al.
Abstract : Introduction: Neo-adjuvant chemotherapy (NACT) in cervical cancer during pregnancy may help in disease control while fetal maturity is reached, before providing a definitive oncological treatment. The objective of this study is to describe obstetric and oncological outcomes in patients diagnosed with cervical cancer stage IB1-IVA (FIGO 2009) during pregnancy, who received this treatment approach. Methods: A multicenter retrospective review was conducted in 12 institutions from 7 Latin-American countries, between January 2007 and December 2018. Data collected included clinical characteristics, NACT agents, definitive treatment, obstetric and oncologic outcomes. Results: Twenty-nine patients were included. Mean age was 33.8 years (+5.2). Twelve (41.4%) women were diagnosed at early stage, and 17 (58.6%) in locally advanced stage. Carboplatin/Paclitaxel was the most frequent combination used (55.2%). Median number of cycles was 3 (1–6). Median gestational age at delivery was 35 (30–39) weeks. All the women delivered by caesarean section and had live births. Two (6.9%) neonates presented low birth weight. There was no evidence of acute toxicity due to chemotherapy. Oncological definitive treatment was chemo-radiotherapy in 15 (51.7%) cases, radical hysterectomy in 12 (41.4%), and just chemotherapy in 2 (6.9%). After a median follow up of 15.6 months (1.8–82.2), three (10.3%) patients recurred, three (10.3%) progressed during treatment, and four (13.8%) died due to disease. Conclusion: NACT during pregnancy is an alternative approach to offer to cervical cancer patients, in order to achieve fetal maturity, before giving definitive treatment; obstetrical and neonatal outcomes were favorable. Oncological outcome deserves further investigation.